New perspectives on chemokines in hepatocellular carcinoma therapy: a critical pathway for natural products regulation of the tumor microenvironment - Ruishi, Xie; Linyi, Xu; Yunfan, Bai; Wenbo, Yu; Xiaoying, Zhang; Xiaoxue, Fang; Difu, Zhu; Xintian, Lan; Ming, Zhu; Haoming, Luo (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is one of the most common primary neoplasms of the liver and one of the most common solid tumors in the world. Its global incidence is increasing and it has become the third leading cause of cancer-related deaths. There is growing evidence that chemokines play an important role in the tumor microenvironment, regulating the migration and localization of immune cells in tissues and are critical for the function of the immune system. This review comprehensively analyses the expression and activity of chemokines in the TME of HCC and describes their interrelationship with hepatocarcinogenesis and progression. Special attention is given to the role of chemokine-chemokine receptors in the regulation of immune cell accumulation in the TME. Therapeutic strategies targeting tumor-promoting chemokines or the induction/release of beneficial chemokines are reviewed, highlighting the potential value of natural products in modulating chemokines and their receptors in the treatment of HCC. The in-depth discussion in this paper provides a theoretical basis for the treatment of HCC. It is an important reference for new drug development and clinical research.